Limits on spin-dependent WIMP-nucleon cross-sections from the first ZEPLIN-II data - Alner, G. J. (2007)
The first underground data run of the ZEPLIN-II experiment has set a limit on the nuclear recoil rate in the two-phase xenon detector for direct dark matter searches. In this Letter the results from this run are converted into the limits on spin-dependent WIMP-proton and WIMP-neutron cross-sections. The minimum of the curve for WIMP-neutron cross-section corresponds to 7×10-2 pb at a WIMP mass of around 65 GeV.